Effect of hemodiafiltration on measured physical activity: primary results of the HDFIT randomized controlled trial. Issue 6 (7th November 2020) - Pecoits-Filho, Roberto; Larkin, John; Poli-de-Figueiredo, Carlos Eduardo; Cuvello-Neto, Américo Lourenço; Barra, Ana Beatriz Lesqueves; Gonçalves, Priscila Bezerra; Sheth, Shimul; Guedes, Murilo; Han, Maggie; Calice-Silva, Viviane; de Castro, Manuel Carlos Martins; Kotanko, Peter; et al.
Abstract: Background: Dialysis patients are typically inactive and their physical activity (PA) decreases over time. Uremic toxicity has been suggested as a potential causal factor of low PA in dialysis patients. Post-dilution high-volume online hemodiafiltration (HDF) provides greater higher molecular weight removal and studies suggest better clinical/patient-reported outcomes compared with hemodialysis (HD). Methods: HDFIT was a randomized controlled trial at 13 clinics in Brazil that aimed to investigate the effects of HDF on measured PA (step counts) as a primary outcome. Stable HD patients (vintage 3–24 months) were randomized to receive HDF or high-flux HD. Treatment effect of HDF on the primary outcome from baseline to 3 and 6 months was estimated using a linear mixed-effects model. Results: We randomized 195 patients (HDF 97; HD 98) between August 2016 and October 2017. Despite the achievement of a high convective volume in the majority of sessions and a positive impact on solute removal, the treatment effect HDF on the primary outcome was +538 [95% confidence interval (CI) −330 to 1407] steps/24 h after dialysis compared with HD, and was not statistically significant. Despite a lack of statistical significance, the observed size of the treatment effect was modest and driven by steps taken between 1.5 and 24.0 h after dialysis, in particular between 20 and 24 h (+197 steps; 95% CI −95 to 488). Conclusions: HDF did not have a statistically significant treatment effect on PA 24 h following dialysis, albeit effect sizes may be clinically meaningful and deserve further investigation. Graphical Abstract: